Bosnia and Herzegovina Pension System Note - World Bank (Washington, DC, 2014)
The Bosnia and Herzegovina (BH) pension system currently consists of two pension funds, each functioning in one o f the two entities making up Bosnia and Herzegovina, the Federation (FBiH) and Republika Srpska (RS). Both pension systems have already undertaken substantial reforms supported by the World Bank. However, critical problems still exist in both systems and will only worsen with time. This note provides an evaluation of the current system and provides some possible reform options. The note is organized as follows: Section 2 contains a brief overview of the historical development of the pension systems, Section 3 contains a brief overview of the current demographics and financial status of the pension funds, Section 4 provides a detailed review of the pension system design parameters in each system, providing international comparisons, Section 5 provides projections of the financial and social consequences of today's parameters, Section 6 provides some reform options which harmonize parameters across the two entities and remove the most obvious disincentives in the current systems, Section 7 provides a longer run view on options for dealing with declining pension coverage among the elderly, and Section 8 concludes.